Evaluation of Health Insurance Patient Satisfaction in Participating in the Referral Back Program for Hypertension Cases at the Community Health Center - Meiningsih Meiningsih; Indasah Indasah; Agusta Dian Ellina (Indonesian Journal of Global Health Research, 2025)
Hypertension is one of the factors contributing to non-communicable diseases that can have a negative impact on an individual's social, economic, and psychological aspects. Therefore, it has been designated as one of the diseases that requires a referral-back program. However, adherence to the referral-back program still needs to be evaluated. This study aims to evaluate the satisfaction of health insurance patients participating in the referral-back program for hypertension cases at Kumpai Batu Atas Health Center. A qualitative descriptive research was applied in phenomenology approach by interviewing 17 primary informants and 2 triangulation informants from the hospital and health center. Data collection includes in-depth interviews, triangulation, and patient medical records. Interviews are interactive and flexible, using probing techniques to explore participants’ experiences. Triangulation with health center staff, physicians, and specialists ensures validity. Data analysis follows reduction, presentation, and conclusion drawing, refining key themes, structuring findings, and verifying conclusions for accuracy. The thematic analysis yielded 4 themes: 1) the situation of referral-back program participants (diagnosed based on signs, symptoms, and predisposing factors. Some dropped out after 2-6 months due to uncertainty about the availability of medication); 2) satisfaction with the quality of service (satisfactory due to fast and accurate service. Professional attitudes were expressed appropriately and in accordance with needs. Clinical competence was displayed with quality and empathy was expressed with a humble attitude); 3) satisfaction with the value referral-back program facilitates access and fast service. Certainty and innovation are the main values for patients); and 4) perceptions of the best desired service (certainty of medication availability, easy administration, and friendly communication are highly desired).